Does selection for growth rate in broilers affect their resistance and tolerance to Eimeria maxima? - Sakkas, Panagiotis; Oikeh, Idiegberanoise; Blake, Damer P; Nolan, Matthew J; Bailey, Richard A; Oxley, Anthony; Rychlik, Ivan; Lietz, Georg; Kyriazakis, Ilias (Veterinary parasitology, 2018)
Chickens exhibit varied responses to infection with Eimeria parasites. We hypothesise that broilers selected for increased growth rate will show lower resistance and tolerance to a coccidian challenge. 288 chickens of fast (F) or slow (S) growing lines were inoculated with 0 (control), 2500 (low-dose), or 7000 (high-dose) sporulated E. maxima oocysts at 13 days of age in two consecutive rounds. Gain and Intake were measured daily and their values relative to BW at the point of infection were calculated over the pre-patent (days 1-4 post-infection), acute (d5-8 pi), and recovery (d9-12 pi) phases of infection to assess the impact of infection. Levels of plasma carotenoids, vitamins E and A, long bone mineralisation, caecal microbiota diversity indices, and histological measurements were assessed at the acute (d6 pi) and recovery stage (d13 pi). In addition, we measured the levels of nitric oxide metabolites and the number of parasite genome copies in the jejunumat d6pi. In absolute terms F birds grew 1.42 times faster than S birds when not infected. Infection significantly reduced relative daily gain and intake (P < 0.001), with the effects being most pronounced during the acute phase (P < 0.001). Levels of all metabolites were significantly decreased, apart from NO which increased (P < 0.001) in response to infection on d6pi, and were accompanied by changes in histomorphometric features and the presence of E. maxima genome copies in infected birds, which persisted to d13pi. Furthermore, infection reduced tibia and femur mineralisation, which also persisted to d13pi. Reductions in measured variables were mostly independent of dose size, as was the level of parasite replication. The impact of infection was similar for S and F-line birds for all measured parameters, and there were no significant interactions between line x dose size on any of these parameters. In conclusion, our results suggest that line differences in productive performance do not influence host responses to coccidiosis when offered nutrient adequate diets.
Keywords: jejunum; Animal Nutritional Physiological Phenomena; Jejunum; krmivo pro zvířata; nemoci drůbeže; potravní doplňky; Bone mineralisation; Eimeria maxima; Carotenoids; karotenoidy; Vitamin E; kur domácí; Tolerance; Vitamin A; fyziologická kalcifikace; fyziologie výživy zvířat; Growth rate; Chickens; zvířata; oxid dusnatý; Poultry Diseases; Calcification, Physiologic; Dietary Supplements; Nitric Oxide; Coccidiosis; vitamin A; Animal Feed; Resistance; Genetic selection; vitamin E; Broiler; kokcidióza; Eimeria; Animals